PENGARUH AKTUALISASI DIRI DAN GAYA HIDUP HANGOUT TERHADAP KEPUTUSAN PEMBELIAN PADA KOPI KONNICHIWA DI KOTA DEPOK TAHUN 2023 - Betty Kartika; Robby Irvawan (JAMBIS : Jurnal Administrasi Bisnis, 2023)
The crowding of coffee shops in the city of Depok is one of the impacts of lifestyle changes and the increasing demand for coffee consumption by the community. Consumers also often make coffee shops as a place to gather with friends, do assignments and working. At the present time self-actualization can be done by following various kinds of current trends such as trends in technology, music, fashion and culture etc. This is increasingly interesting to study in order to find out how psychological and sociological theories influence consumer purchasing decisions, which are considered to be more consumptive and the higher the enthusiasm for coffee shops. The purpose of this study was to determine the effect of self-actualization and hangout lifestyle on purchasing decisions for Konnichiwa coffee in Depok City. This type of research is quantitative, non-probability sampling technique with incidental sampling method using 110 respondents who have made purchases at Konnichiwa coffee. Data collection used a questionnaire on Googleform with a Likert scale of 1-5 with 22 statement items. The data analysis technique uses multiple linear regression with the assistance of SPSS 25. The results of this study indicate that the self-actualization variable (X1) has a positive and significant influence on purchasing decisions. The hangout lifestyle (X2) has a positive and significant influence on purchasing decisions. Self-actualization (X1) and hangout lifestyle (X2) have a simultaneous influence on purchasing decisions on konnichiwa coffee in Depok City.